Synthesis of 4-(2-fluorophenyl)-7-methoxycoumarin: experimental and computational evidence for intramolecular and intermolecular C–F···H–C bonds - Mzozoyana, Vuyisa; van Heerden, Fanie R.; Grimmer, Craig (Beilstein Journal of Organic Chemistry, 2020)
4-(2-Fluorophenyl)-7-methoxycoumarin (6) was synthesized by Pechmann reaction under mild conditions via a three-step reaction. The solution-state 1H NMR spectra of 6 showed a strong intramolecular interaction between F and H5 (JFH = 2.6 Hz) and 13C NMR suggested that this C–F···H–C coupling is a through-space interaction. The 2D 19F-{1H} HOESY and 1H-{19F} 1D experiments were done to confirm this F···H interaction. The single crystal X-ray structure and the DFT-optimized structure showed that the fluorinated phenyl ring favors the orientation with the fluorine atom closer to H5 than H3. The X-ray structure also showed the existence of the intermolecular C–F···H–C interaction.
Keywords: DFT; F···H hydrogen bond; fluorinated phenylcoumarin; Pechmann reaction; through-space coupling